The influence of mentoring and practicality book toward religiousity development of the third year students in class of multimedia of SMK N 1 Pengasih Kulon Progo in 2008/2009 academic year - Umi Masruroh (Fak. Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga, 2009)
irh,1/ws.c.1